Development and Validation of Perception of Seating Ergonomics Questionnaire: A Study on Klang Valley Drivers in Malaysia - Yap, Choy Min; Mohd Rasdi, Hanif Farhan; Harun, Dzalani; Lim, Wen Xin (UI Scholars Hub, 2023)
Driving is an instrumental activity of daily living that has become an essential mode of transportation. Good ergonomic practices are vital to ensure successful driving. This study aimed to develop and validate a questionnaire that could be used to determine how personal, environmental, and occupational factors influence drivers' perceptions of seating ergonomics. This cross-sectional study was conducted in June-July 2022 among 250 drivers in the Klang Valley, Malaysia, recruited via an online survey. The participants completed the questionnaire by assessing different constructs in the Person-Environment-Occupationmodel and perceptions of seating ergonomics. Exploratory factor analysis (EFA) was conducted, followed by a path analysis. Test-retest reliability wasassessed in 30 participants. The final EFA generated a four-factor structure that accounted for 61.69% of the variance. The final version of the questionnairecontained 19 items. The Cronbach's alpha values for all the constructs were above 0.7, and all the intraclass correlation coefficients were above 0.8. Basedon the path analysis results, personal and occupational factors emerged as significant predictors for drivers' perceptions of seating ergonomics. The developed questionnaire was valid and reliable.